Sodium-Glucose Cotransporter-2 (SGLT-2) Attenuates Serum Uric Acid (SUA) Level in Patients with Type 2 Diabetes - Mazhar Hussain; Asim Elahi; Abid Hussain; Javed Iqbal; Lubna Akhtar; Abdul Majid (Journal of Diabetes Research)
Background. Hyperuricemia has a strong association with diabetes mellitus. Hyperuricemia can lead to cardiovascular and renal complications in patients with diabetes. The goal of this study was to compare the effect of sodium-glucose cotransporter-2 (SGLT-2) inhibitors dapagliflozin and empagliflozin on serum uric acid (SUA) levels in patients with type 2 diabetes against traditional oral antihyperglycemic drugs (OADs). Methods. In this double-blind randomized controlled trial, 70 patients with type 2 diabetes and elevated SUA levels were assigned to two treatment groups. Patients in group A received SGLT-2 inhibitors tablet dapagliflozin 5 mg to 10 mg and empagliflozin 10 mg to 25 mg. Group B patients received OADs such as glimepiride, metformin, sitagliptin, gliclazide, and glibenclamide as monotherapy or combination therapy. The changes in SUA level were primary end points while changes in body weight and body mass index (BMI) from baseline to end point were secondary end points. Results. After four weeks of treatment, we noted a significant reduction of mean SUA levels in the SGLT-2 inhibitor group from 7.5±2.5 to 6.3±0.8 mg/dl versus comparator group from 7.1±1.8 to 6.8±2.2 mg/dl (p=0.001). Mean body weight was significantly reduced in the SGLT-2 group from 82±10.4 to 78±12.5 kg versus comparator group from 78±13.2 to 79.2±9.7 kg (p=0.001). Similarly, the mean BMI of patients in the SGLT-2 group was significantly reduced from 25.7±3.2 to 24.2±3.2 kg/m2 versus comparator group from 27.5±4.2 to 28±3.6 kg/m2 (p=0.002). Conclusion. SGLT-2 inhibitors have a strong potential to decrease SUA levels in patients with type 2 diabetes.